EFEKTIFITAS PELAKSANAAN BUSINESS DEVELOPMENT SERVICES (BDS) TERHADAP KEPATUHAN WAJIB PAJAK UMKM (Studi kasus pada UMKM yang terdaftar di KPP Pratama Batu) - Safira Koesherawati; Afifudin Afifudin; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the effectiveness of the implementation of Business Development Services (BDS) on taxpayer compliance. This research is a quantitative research using two types of data, namely primary data and secondary data. Primary data obtained from questionnaires and measured using a Likert scale and secondary data obtained from taxpayer data in the working area of KPP Pratama Batu. The population in this study are individual UMKM taxpayers who have run the Business Development Services (BDS) program in the work area of KPP Pratama Batu. The method of determining the sample using purposive sampling method. The data analysis technique used SPSS 16.0.The results of this study indicate: 1) The variable knowledge of taxation, knowledge of bookkeeping and tax calculations have a simultaneous effect on UMKM taxpayer compliance, 2) Hypothesis test results indicate that tax knowledge affects UMKM taxpayer compliance, 3) Hypothesis test results indicate that knowledge bookkeeping and tax calculations have no effect on UMKM taxpayer compliance.Keywords: Effectiveness, Business Development Services, Tax Knowledge, Tax Bookkeeping, Tax Calculation, Compliance.